Consumer Awareness of Sustainable Margarine - Parikesit, Bonifasius; Yudithadewi, Dien; Tantri, Irene; Yuliastanti, Erika Dwi (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Indonesia holds a prominent position as both a producer and consumer of margarine. Research indicates a growing interest among Indonesian consumers in opting for sustainable products, demonstrating a willingness to pay more in such choices. This study delves into the consumption patterns surrounding palm oil-based margarine, aiming to pinpoint the factors influencing consumers towards sustainable margarine option. The selection of margarine aligns with commonly consumed household products. Moreover, the choice of research subject intertwines with the significance of raw materials sourced from commodities that play pivotal roles in economic, social, and environmental spheres. Employing a qualitative methodology, this research engages observation and interviews with 36 participants, utilizing the Focus Group Interview (FGI) technique. The findings underscore that 33 respondents prioritize brand preference when selecting margarine, while three base their choice on habitual consumption patterns. Interestingly, price and eco-labels did not emerge as significant factors influencing purchase decisions among the respondents. However, a notable majority expressed a readiness to transition to sustainable options within their preferred brand, indicating a willingness to pay a premium of up to 10 percent for eco-labelled margarine. Intriguingly, all participants remained unaware of the availability of sustainable margarine options, shedding light on a potential gap in consumer awareness within the market.